2006
DOI: 10.1074/jbc.m511592200
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Myosin VIIA Is a High Duty Ratio Motor with a Unique Kinetic Mechanism

Abstract: Mutations of myosin VIIA cause deafness in various species from human and mice to Zebrafish and Drosophila. We analyzed the kinetic mechanism of the ATPase cycle of Drosophila myosin VIIA by using a single-headed construct with the entire neck domain. The steady-state ATPase activity (0.06 s ؊1 ) was markedly activated by actin to yield V max and K ATPase of 1.72 s ؊1 and 3.2 M, respectively. The most intriguing finding is that the ATP hydrolysis predominantly takes place in the actin-bound form (actin-attache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…Previous in vitro studies of Drosophila myosin VIIA have suggested that myosin VIIA can be a cargo-transporting motor because it is a high duty ratio motor (13) and the forced dimer construct of the tail-truncated Drosophila myosin VIIA moves processively in vitro (14). In the present study, we showed that human myosin VIIA can transport its cargo complex in ARPE-19 cells, thus functioning as a cargo transporter.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Previous in vitro studies of Drosophila myosin VIIA have suggested that myosin VIIA can be a cargo-transporting motor because it is a high duty ratio motor (13) and the forced dimer construct of the tail-truncated Drosophila myosin VIIA moves processively in vitro (14). In the present study, we showed that human myosin VIIA can transport its cargo complex in ARPE-19 cells, thus functioning as a cargo transporter.…”
Section: Discussionsupporting
confidence: 48%
“…These results suggest that human myosin VIIA does not form a stable dimer in cells. It was reported previously that Drosophila myosin VIIA is a high duty ratio motor suitable for a processive movement (13), and the forced dimer of the tail-truncated Drosophila myosin VIIA can move processively in vitro (14). Therefore, we asked whether human myosin VIIA may move on actin filaments in vivo once it forms a dimer.…”
Section: Resultsmentioning
confidence: 99%
“…The actin-dependent MgATPase activity of myosin 7a-FL shows important differences compared with that of the S1 fragment reported previously (14,15). The V max of both constructs is Ϸ1 s Ϫ1 , but myosin 7a-FL has a high K ATPase of 30 Ϯ 12 M, unlike S1 where the K ATPase is 1.1 Ϯ 0.1 M (Fig.…”
Section: Expression and Purification Of Full-length Myosin 7a With Camentioning
confidence: 72%
“…To express the recombinant myosin Vc proteins, Sf9 cells were co-infected with two viruses expressing myosin Vc heavy chain and calmodulin. The expressed proteins were purified through an anti-FLAG M2 affinity column (Sigma) as previously described (29). The purified proteins were dialyzed against buffer A (25 mM KCl, 20 mM MOPS-KOH (pH 7.5), 2 mM MgCl 2 , 1 mM EGTA, and 1 mM DTT).…”
Section: Methodsmentioning
confidence: 99%